Minimally Invasive Techniques of Oculofacial Rejuvenation. - Bosniak, Stephen (Thieme, 2011)
Seeking ways to improve their appearance with little or no ''down time, '' more and more patients are turning to their physicians for the newest, non-invasive technologies. Here is your complete guide to the most effective, popular, and safe minimally invasive, surgical, and peri-oral rejuvenation techniques. It provides key information on incorporating filling agents, combination therapies, intense pulsed light (IPL), chemical peels, and radiofrequency devices into everyday practice. Tactics for surgical procedures using lasers and small incisions further expand your treatment options. Yo.